Efficacy of Alpha Lipoic Acid Supplementation In Chemotherapy-Induced Peripheral Neuropathy - Mediarty Syahrir; Yenny Dian Andayani; Norman Djamaludin; Erty Sundarita Maksudin; Putri Farissa Muharramah; Kgs. M. Rosyidi; Hasnawi Haddani; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background. Chemotherapy-induced peripheral neuropathy is a side effect of several chemotherapy drugs and a significant cause of chronic pain in cancer patients, which affects patients' long-term quality of life. The neurotoxic chemotherapy agents most reported to cause neuropathic pains are platinum and taxane. This study aimed to determine the efficacy of alpha-lipoic acid supplementation in chemotherapy patients. Methods. This study used a randomized, double-blind clinical trial in the oncology haematology clinic in the Department of Internal Medicine at Mohammad Hoesin General Hospital Palembang from November 2018 to July 2019. Samples were taken from patients who met the inclusion criteria and signed informed consent forms to join the study. This studyused SPSS version 22.0 for Windows to analyze the data. Results. This research studied 30 subjects who were divided into alpha lipoic acid groups and placebo groups with 15 samples each. The alpha-lipoic acid group showed a significant decline in the Toronto Clinical Scoring System (TCSS) after treatment (p = 0.000) compared to the placebo group (p = 0.164). Conclusions. Treatment with a 600 mg single dose each day of alpha-lipoic acid for 12 weeks effectively improved patients condition significantly.